How to integrate physiological data from wearables in treatment of personality disorders: a narrative review - Lans, Luuk L.; Huijbregts, Klaas M. L.; Westerhof, Gerben J.; Haeyen, Suzanne W.; Derks, Youri P. M. J.; Noordzij, Matthijs L. (Frontiers in Psychiatry, 2025)
In recent years, stress-monitoring innovations using wearable technology have entered the market. One innovation is biocueing, a process where patients receive real-time feedback on passive monitoring of significant changes in their physiological data, such as (additional) heart rate, heart rate variability or skin conductance. This technology offers potential for patients with borderline personality disorder, as they often report severe stress, difficulties in emotion regulation and low levels of emotional- and body awareness. Yet, currently there is no clear direction on when and how to fit these technologies, and physiology in general, into treatments for borderline personality disorder. We provide a comprehensive review on how and to what extent evidence-based treatments (Transference Focused Psychotherapy, Mentalization Based Treatment, Schema Therapy, Dialectical Behavior Therapy), and their underpinning theories provide guidance and predictions for integrating these technologies. Only Dialectical Behavior Therapy provide a theoretical framework that includes physiology, as well as interventions that actively target physiological data, whereas the other evidence-based treatments largely disregard physiology. Other promising developments are Creative Arts and Psychomotor Therapies and the Polyvagal theory, as they target bodily sensations and physiology more directly. Four avenues for future research and integration of psychophysiological theory and wearable technology in treatment are discussed: abandoning physiological data and technology, keeping a human in the loop, machine-learning biocueing interventions, or biomonitoring devices as long-term (mental) health monitors.